Functional Properties of Sorghum (S. bicolor L.) - Pigeonpea (Cajanus cajan) Flour Blends and Storage Stability of a Flaked Breakfast Formulated from Blends - Mbaeyi-Nwaoha, I.E.; Onweluzo, J.C. (Pakistan Journal of Nutrition, 2013)
The possibility of replacing treated (SSF) and untreated (USF) sorghum flour with different ratios of pigeon pea flour (CCF) was investigated. Their functional properties (Bulk density, viscosity, least gelation concentration, water absorption capacity, reconstitution time, pH and particle size distribution) were examined. Bulk density increased with the increased supplementation of pigeon pea flour the formulation resulting in a denser product. Sprouting and pregelatinization increased in the viscosity of the flour compared to the untreated samples. The least gelation concentration ranged between 0.2-0.4 g/g. Both pregelatinization and sprouting increased the strength of the gel of the treated samples unlike the untreated ones. The pregelatinized flours and their flour blends absorbed more water (7.00-8.00 g/ml) than the sprouted samples (7.00-7.50 g/ml) which caused some starch gelatinization and increased porosity of the corneous endosperm fragments. Higher absorption and lower solubility led to higher viscosity (p<0.05) or cooked paste viscosity. Untreated samples show marginally high oil absorption capacity of between 2.66 g/ml-3.23 g/ml, the pregelatinized flour and their composites showed higher (p<0.05) oil absorption capacity (2.66-3.04 g/ml) while the sprouted sample ranged between 2.85-3.23 g/ml. However, sample SSF + CCF (100:0) took 92.5 seconds to reconstitute while. PSF+CCF (60:40) took 20.0 seconds probably be due to heat treatment during pregelatinization which increased the action of alpha- and beta- amylases and modified the native starch. PSF + CCF (100:0) gave the least pH of 4.25 while USF + CCF (80:20) gave the highest value of 5.87 (all in the acidic range). Thus, the blending of the sorghum and pigeon pea could perform favorably in the formulation of breakfast cereal and infant foods. A high quality flaked breakfast cereal was prepared from sprouted and pregelatinized, packaged and stored on a shelf at room temperature (25±2°C) for 90 days. The storage stability was evaluated by analyzing periodically for changes in physical properties (water activity, colour change, temperature, relative humidity), chemical changes (development of peroxides and rancidity) and microbiological changes. Result show that colour, temperature, relative humidity, peroxide values and Thiobarbituric Acid (TBA) values remain practically constant during storage. Also, no significant (p>0.05) changes were observed in TBA values, peroxide value, water activity and moisture absorption of the packaged products during storage. The water activity (aw) of all products was between 0.435-0.785 and none were attracted by microorganisms over the 3 months. The products did not exhibit bacterial, coliform and mold growth, especially for those in the bulk packages, which served as a double barrier to moisture, oxygen and other gases. Thus, the bulk packages are advantageous over the single packs thereby suggesting that the former could lead to better keeping quality for these products and the products also maintained their crispiness. By implication from the shelf life projection studies, the formulated products from the treated flours might be stored in high density polythene bags for up to six months or more at ambient conditions.